2012
DOI: 10.1186/1556-276x-7-491
|View full text |Cite
|
Sign up to set email alerts
|

Intersubband terahertz transitions in Landau level system of cascade GaAs/AlGaAs quantum well structures in strong tilted magnetic field

Abstract: The tunable terahertz intersubband Landau level transitions in resonant tunneling cascade quantum well structures are considered. The way of lifting the selection rule forbidding the inter-Landau level terahertz transitions of interest by applying a magnetic field tilted with respect to the structure layers is proposed. The importance of asymmetric structure design to achieve considerable values of transition dipole matrix elements is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…1 2 However, there is the selection rule ááD = ññ n 0 which forbids any transitions with D ¹ n 0. This selection rule can be violated by tilting the magnetic field with respect to the layers of quantum well structure [17,19]. The numerical calculations carried out in the [19] for some fixed quantum well structure while varying the magnitude and direction of the magnetic field, demonstrated that the intensity of peaks induced by transitions with D ¹ n 0 can exceed that of the peak with D = n 0, attaining the values close to those in the absence of a magnetic field.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…1 2 However, there is the selection rule ááD = ññ n 0 which forbids any transitions with D ¹ n 0. This selection rule can be violated by tilting the magnetic field with respect to the layers of quantum well structure [17,19]. The numerical calculations carried out in the [19] for some fixed quantum well structure while varying the magnitude and direction of the magnetic field, demonstrated that the intensity of peaks induced by transitions with D ¹ n 0 can exceed that of the peak with D = n 0, attaining the values close to those in the absence of a magnetic field.…”
Section: Introductionmentioning
confidence: 97%
“…The other appealing aspect is a possibility of tuning the frequency of optical transitions between Landau levels of different subbands [17,18]. The frequency of transition between n 1 th LL in n 1 th subband (LL n ( ) n , 1 1 ) and n 2 th LL in n 2 th subband (LL n ( ) n , 2 2 )   w e w = D + -( ) ( ) n n 1 1 2 (where e D is intersubband spacing and w = / eB m c w is the cyclotron frequency) can be tuned by varying magnetic field strength, if D = -¹ n n n 0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up until now, the best THz QCL is based on GaAs, whose maximum operating temperature is about 200 K due to the low LO-phonon energy (36 meV) of GaAs [3, 4]. With the assistance of a magnetic field, this temperature can be raised up to 225 K. However, this method is unsuitable for wide-spread applications [5, 6]. When the temperature increases, electrons in the upper-level state can acquire enough thermal energy for activating non-radiative relaxations via LO-phonon emission towards the lower level state, hence destroying the population inversion.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the selection rule forbidding the transition of interest in a magnetic field directed perpendicularly to the structure layers can be effectively suppressed in tilted magnetic field if asymmetric potential along the structure axis is simultaneously applied [3]. A periodic cascade quantum well structure with period consisting of two strongly coupled wells with different widths was considered as one of the possible solutions.…”
mentioning
confidence: 99%